Martin Fourcade`s physiological adaptations - 10 years of training and monitoring - Schmitt, L. (Congress of Youth & Winter Sports, 2020)
Präsentation des Trainings von Martin Fourcade und der physiologischen Anpassungen, die damit im Zusammenhang stehen.